Introduction to Black Hole Physics - Frolov, Valeri P author; Zelnikov, Andrei (Oxford : Oxford university press, 2011)
This book is about black holes, one of the most intriguing objects of modern Theoretical Physics and Astrophysics. For many years, black holes have been considered as interesting solutions of the theory of General Relativity with a number of amusing mathematical properties. Now after the discovery of astrophysical black holes, the Einstein gravity has become an important tool for their study. This self-contained textbook combines physical, mathematical, and astrophysical aspects of black hole theory. Pedagogically presented, it contains 'standard' material on black holes as well as relatively new subjects such as the role of hidden symmetries in black hole physics, and black holes in spacetimes with large extra dimensions. The book will appeal to students and young scientists interested in the theory of black holes.
References 463-476p.; Index 477-488p.
Keywords: Astronomy; Black holes; Cosmology; Astro physics